Association Between High Sensitivity Cardiac Troponin and All-Cause and Cardiovascular Mortality in Adults at Risk of Non-Alcoholic Fatty Liver Disease: A Cohort Study - Enfa Zhao; Hang Xie; Yuan Gao; Xiaolin Wen; Bingtian Dong; Chaoxue Zhang (Global Heart)
Objective: Cardiovascular disease (CVD) is the leading cause of death among patients with non-alcoholic fatty liver disease (NAFLD). This study investigates the association between high-sensitivity cardiac troponin (hs-cTn) levels and mortality in adults at risk of NAFLD in a representative U.S. population sample. Methods: Among participants aged 18 years and older in the 1999–2004 National Health and Nutrition Examination Survey, we measured high-sensitivity troponin T using a single assay (Roche) and high-sensitivity troponin I using three assays (Abbott, Siemens, and Ortho). Myocardial injury was identified by elevated levels of hs-cTn. Mortality outcomes were determined through linkage with the National Death Index database, with follow-up until December 31, 2019. A multivariable Cox proportional hazards model was used to evaluate the associations between myocardial injury and mortality in the NAFLD population. Sensitivity analyses were conducted to assess the robustness of the main findings. Results: A total of 2581 at risk of NAFLD were included in this observational study, with myocardial injury identified in 7.01%. Over a median follow-up of 16.7 years, 937 all-cause deaths occurred, including 319 cardiovascular disease-related deaths. NAFLD individuals with myocardial injury had worse survival rates at 5, 10, and 15 years compared to those without myocardial injury. After adjusting for baseline characteristics, myocardial injury was associated with an increased risk of all-cause mortality (adjusted Hazard Ratio [aHR] 1.785, 95% CI 1.494–2.134, P < 0.001) and cardiovascular mortality (aHR 2.155, 95% CI 1.606–2.893, P < 0.001). Conclusion: This large, nationally representative study demonstrates that myocardial injury, defined by elevated hs-cTn levels, is independently associated with increased all-cause and cardiovascular mortality risks in the adult population at risk of NAFLD in the United States. This association persisted after adjusting for various factors and in patients without pre-existing cardiovascular disease. The Siemens hs-cTn I assay demonstrated the strongest association with all-cause mortality. These findings highlight the potential of hs-cTn as a valuable prognostic marker in NAFLD patients, even in those without clinically apparent cardiovascular disease. Routine hs-cTn assessment may aid in risk stratification and guide targeted interventions to reduce mortality risk in this population.